Microbial pelagic metabolism and CDOM characterization in a phytoplankton-dominated versus a macrophytedominated shallow lake - Torremorell, Ana María (2015)
Dominant primary producer in macrophyte- or phytoplankton-dominated shallow lakes might imply differences in dissolved organic carbon (DOC) composition. We compared chromophoric dissolved organic matter (CDOM), plankton respiration (R), and bacterial (BP) and primary production (PP), in two contrasting shallow lakes. We hypothesized that DOC from the macrophyte-dominated lake would be qualitatively inferior, so that it can support a lower yield than DOC from the phytoplankton-dominated one. Macrophyte-dominated lake had more humic and aromatic CDOM, though molecular weight was similar in both lakes. A clear synchronism between lakes was observed in mean depth and several CDOM absorption coefficients, suggesting an external driver of the variation in DOC concentration and CDOM quality. The positive BP-PP and BP-Chl-a correlations in the macrophyte-dominated lake point out to a dependence of bacteria on phytoplankton for a supply of labile DOC. In turn, BP in the phytoplankton-dominated lake was balanced with grazing by HF (heterotrophic flagellates). The significantly higher HB:DOC and HF:DOC carbon ratios in the phytoplankton-dominated lake also suggest that better DOC quality would mean relatively more efficient C transfer to higher trophic levels. According to PP:BP and PP:R ratios both lakes should be considered autotrophic, although the macrophyte-dominated lake would be comparatively more heterotrophic.